ASESMEN OTENTIK BERBASIS TEKNOLOGI PLICKERS BAGI SISWA SD MASA PANDEMI COVID-19 - Sri Sulistyorini; Nugraheti Sismulyasih; Trimurtini; Isa Ansori; Marjuni; Eko Purwanti (Bahasa Indonesia, 2021)
Abstract Assessment of learning outcomes often referred to by students as replays becomes something scary for students. There needs to be effort and innovation to change the stigma of students towards replay. If the replay is packaged interestingly, then the student will have enthusiasm and motivation towards the replay because the student feels as a pleasant thing so it will have a positive impact on the student's learning outcomes. The purpose of this community service activity is to improve the skills of elementary school teachers in conducting assessment analysis of learning results based on information technology. Especially intended to develop skills to elementary school teachers in the analysis of learning results based on plickers technology through training and mentoring activities. Training materials include the introduction of plickers, technical development of plickers, and the practice of using plickers. A sample of 30 teachers at SD Ngaliyan 01 was taken purposive random sampling. Training methods include q&A, discussions, assignments, portfolios, pretes, posts and preparation of follow-up plans. The results of community activities show the following: the average attendance of participants was 96.3% with full participation. Pretest & posttest results showed participants an average of 59.17. The average postest was 89.8. The average community service team attendance is 100%. Presentation of material is carried out by discussion method, assignment, demonstration and lecture with a handout of serving material. 100% certificate kepesertan workshop 36 JP. There is an increase in participants' scores from pretest to postest, it can be concluded that there is a development of the skills of elementary school teachers in the assessment of student learning results based on plickers technology in Ngaliyan Sub-district of Semarang. Abstrak Asesmen hasil belajar yang sering disebut oleh siswa sebagai ulangan menjadi sesuatu hal yang menakutkan bagi siswa. Perlu adanya upaya dan inovasi untuk mengubah stigma siswa terhadap ulangan. Apabila ulangan dikemas dengan menarik, maka siswa akan memiliki antusias dan motivasi terhadap ulangan karena siswa merasakan sebagai hal yang menyenangkan sehingga akan berdampak positif terhadap hasil belajar siswa. Tujuan dari kegiatan pengabdian masyarakat ini adalah meningkatkan keterampilan guru sekolah dasar (SD) dalam melakukan analisis asesmen hasil belajar berbasis teknologi informasi. Khususnya dimaksudkan mengembangkan keterampilan kepada guru-guru SD dalam analisis asesmen hasil belajar berbasis teknologi plickers melalui kegiatan pelatihan dan pendampingan. Materi pelatihan meliputi pengenalan plickers, teknis pengembangan plickers, dan praktik penggunaan plickers. Sampel kegiatan pengabdian masyarakat ini sebanyak 30 guru di SD Ngaliyan 01 yang diambil secara purposive random sampling. Metode pelatihan meliputi tanya jawab, diskusi, penugasan, portofolio, pretes, postes dan penyusunan rencana tindak lanjut. Hasil kegiatan masyarakat menunjukkan hal-hal sebagai berikut: rata-rata kehadiran peserta 96,3% dengan partisipasi penuh. Hasil pretest & postest peserta menunjukkan rata- rata 59,17. Adapun perolehan nilai rata- rata pada postest adalah 89,8. Kehadiran tim pengabdian masyarakat rata-rata 100%. Penyajian materi dilaksanakan dengan metode diskusi, penugasan, demonstrasi dan ceramah dilengkapi handout materi sajian. Diberikan sertifikat kepesertaan workshop setara 36 JP. Terjadi peningkatan nilai peserta dari pretest ke postest, dapat disimpulkan bahwa ada pengembangan keterampilan guru SD dalam analisis asesmen hasil belajar siswa berbasis teknologi plickers di Kecamatan Ngaliyan Kota Semarang.